Time and the Ancestors Aztec and Mixtec Ritual Art - Jansen, Maarten (The Early Americas: History and Culture, 2017)
Time and the Ancestors: Aztec and Mixtec Ritual Art combines iconographical analysis with archaeological, historical and ethnographic studies and offers new interpretations of enigmatic masterpieces from ancient Mexico, focusing specifically on the symbols and values of the religious heritage of indigenous peoples.; Readership: Scholars and students working on the archaeology, art, history and anthropology of Mexico, as well as the general public interested in Mexican indigenous culture.